Investigating the early age crack resistance of concrete treated with silane-modified zeolite powder - Yuan Zhou; Sheliang Wang; Ling Chen; Juan Wang (Alexandria Engineering Journal)
This study investigates the efficacy of silane-modified zeolite powder in enhancing the early age crack resistance of concrete. Three concrete mixes were evaluated: a reference mix, a 20 % zeolite replacement mix, and a silane-modified zeolite mix. The silane-zeolite mix demonstrated significant improvements, extending the time to crack by 70 % compared to the reference mix (from 11.2 to 19.1 hours). Mechanical strength tests revealed a 58 % increase in first-crack strength for the silane-zeolite mix over the reference mix. Water absorption tests showed that the silane-zeolite mix absorbed 42 % less water than the reference mix, indicating a denser microstructure. Microscopic analyses confirmed these findings, revealing a more refined pore structure with reduced microcrack frequency and width in the silane-zeolite mix. These results highlight the potential of silane-modified zeolite in improving concrete durability and longevity.